Superconductivity at 7.3 K in the 133-type Cr-based RbCr3As3 single crystals. (15th January 2018) - Liu, Tong; Mu, Qing-Ge; Pan, Bo-Jin; Yu, Jia; Ruan, Bin-Bin; Zhao, Kang; Chen, Gen-Fu; Ren, Zhi-An
Abstract: Here we report the preparation and superconductivity of the 133-type Cr-based quasi–one-dimensional (Q1D) RbCr3 As3 single crystals. The samples were prepared by the deintercalation of Rb + ions from the 233-type Rb2 Cr3 As3 crystals which were grown from a high-temperature solution growth method. The RbCr3 As3 compound crystallizes in a centrosymmetric structure with the space group P 63 / m (No. 176) different from its non-centrosymmetric Rb2 Cr3 As3 superconducting precursor, and the refined lattice parameters are and . Electrical resistivity and magnetic susceptibility characterizations reveal the occurrence of superconductivity with an interestingly higher onset T c of 7.3 K than other Cr-based superconductors, and an estimated high upper critical field H c 2 (0) about 72.4 T in this 133-type RbCr3 As3 crystals.